Exploring the connection between odour and clothing disposal. Issue 11 (15th October 2021) - McQueen, Rachel H.; Moran, Lori J.; Cunningham, Cassandra; Hooper, Peter M.
Abstract: Increasing textile waste poses a significant environmental problem. There are many motivating factors that can influence a person's choice about when and how to dispose of unwanted clothing. The development and persistence of odour within clothing may be one such factor. The purpose of this study was to explore the relationship between clothing odour and disposal behaviour. In particular, whether consumers dispose of odorous clothing differently from non-odorous clothing. A questionnaire was developed and distributed to a convenience sample through social networks. Responses from 529 consumers residing in Canada and the United States were analysed. The majority of respondents (98.7%) have perceived odour in a clothing item at some point. Of these, approximately half had gotten rid of an article of clothing at some time because it became too odorous to wear. Odour was not a major reason for consumers to discard their clothing. However, when odour was a reason for disposal, respondents reported they were less likely to donate, give-away or sell odorous clothing and more likely to throw odorous clothing items directly into the trash. Therefore, although persistent odour in clothing plays only a minor role on sustainable disposal behaviour, when odour is a motivating factor for discard it leads to less sustainable disposal practices.